PENGARUH PEMBERIAN BERBAGAI WARNA LAMPU PRIMER KONDISI TERHADAP SALURAN PENCERNAAN AYAM PEJANTAN FASE GROWER: THE EFFECT OF PROVIDING VARIOUS COLORS OF PRIMARY LIGHTS ON THE MALE CHICKEN DIGESTIVE TRACT IN GROWER PHASE - Rachmadi, Bayu Dwi; Wulandari, Eudia Christina; Purwadi, Purwadi (Universitas Boyolali, 2023)
Consumption of chicken meat as a popular source of protein, is widely used in Indonesian and foreign cuisine. The Central Bureau of Statistics (BPS) shows that the average weekly consumption per capita of chicken meat in Indonesia is 0.14 kg. indicating an increase of 7.69% since 2020, and consumption of chicken meat in 2011-2021 with the highest growth rate of 19.76% was recorded in 2014 as the highest increase. According to BPS records, chicken meat production in Indonesia this year will reach 3.42 million tonnes. Chicken meat is a very popular animal food source, and usually comes from broiler or real chicken meat. Lighting is the integration of vision, including visual acuity and color differentiation. This study aims to determine the effect of different lighting colors on the digestive tract pH of bulls, ration consumption, body weight gain and mortality.The aim of the study was to determine the benefits of using light on ration consumption, BBB, mortality and hydrogen potential in the digestive tract of layered male chickens at grower phase / 11-20 days old. This research was conducted from 27 March 2022 to 16 April 2022. Analysis of the pH (potential hydrogen) of the digestive tract was carried out at the Poultry Laboratory, Boyolali University, Faculty of Agriculture and Animal Husbandry. The feed used is Commercial feed brand SA 571 NS Sido Agung Group.The design in this study used a completely randomized design (CRD) with 6 treatments, 7 replications. Each replicate consisted of 4 experimental units. The RAL experiment used 168 male chickens aged 11 days. The results showed that the effect of different lighting colors had no significant effect (P>0.05) on feed consumption, ADG, mortality and pH of the digestive tract of male chickens.The conclusion of the research results from statistical data using various variations of lamps has no significant effect on feed consumption, daily body weight gain, mortality and digestive tract pH.Key words : Rooster, Lighting, Ph Gastrointestinal Tract.